Economics of Tea Plantation in Non-Estate Sector: The Impact of Small Tea Plantations on Assam's Economy and Social Structure (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The tea plantations in the Northeast Indian Territory of Assam, dispatched by the British provincial system during the nineteenth century, had extensively changed the financial profile of the state. Its effect on the state's laborer economy, be that as it may, was enervating. Constrained by the British organizations, the plantation sector saw barely any neighbourhood grower, albeit a part of the Assamese workers generally occupied with tea development in their homestead taking things down a notch. After India's freedom, numerous Indian business visionaries entered the plantation sector generally on account of the takeoff of the British grower. The Assamese business people thought that it was hard to imitate this because of absence of capital. Since the 1970s, notwithstanding, a huge segment of the nearby little and center workers, as a piece of a cognizant drive, took to little tea plantation (STP). The most recent twenty years have seen an emotional development in the number of such little grower, which has achieved a significant change in the provincial social scene of Assam.